Energy storage element
By using a negative electrode with a curved folding structure and laminating the negative electrode active material layer in a non-pressure state with solid graphite particles, the issue of the active material layer falling off is addressed, resulting in improved stability and performance of the storage element.
Patent Information
- Application Number
- JP2022507184
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-11
- Filing Date
- 2021-03-08
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2041-03-08
AI Technical Summary
The negative electrode active material layer tends to fall off when the negative electrode has a curved folding structure, particularly when using graphite as the negative electrode active material.
The storage element incorporates a negative electrode with flat portions and a curved folding portion, where the negative electrode active material layer is laminated in a non-pressure or low-pressure pressing state, using solid graphite particles with an aspect ratio of 1 to 5, and ensuring a surface roughness ratio Q2/Q1 of 0.90 or more on the negative electrode substrate.
This configuration effectively prevents the negative electrode active material layer from falling off, even with a curved folding structure, by minimizing stress and ensuring uniform expansion during charging, thus enhancing the stability and performance of the storage element.
Smart Images

Figure 0007673742000002 
Figure 0007673742000003 
Figure 0007673742000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an energy storage element. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion non-aqueous electrolyte secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally include an electrode body having a pair of electrodes electrically isolated by a separator, and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the two electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as storage elements other than non-aqueous electrolyte secondary batteries.
[0003] A typical configuration of such an electric storage element has electrodes (positive and negative electrodes) in which an electrode active material layer containing an electrode active material is held on an electrode substrate. Carbon materials such as graphite are used as the negative electrode active material of the electric storage element (see Patent Document 1). Meanwhile, a lithium ion secondary battery has been known in which one of the negative and positive electrode plates is stacked in a zigzag shape by being alternately folded (see Patent Document 2). The electrode plate having this zigzag stacked structure is less affected by the misalignment of the negative and positive electrode plates, and is characterized by a high short circuit suppression effect since electrode chips are less likely to be generated compared to rectangular electrode plates. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 2005-222933 [Patent Document 2] Japanese Patent Application Publication No. 2014-103082 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the inventors have confirmed that when the negative electrodes are stacked in a curved folded structure and graphite is further used as the negative electrode active material, there are occasional cases in which the negative electrode active material layer falls off from the negative electrode substrate.
[0006] The present invention has been made in light of the above circumstances, and has an object to provide an energy storage element in which falling off of a negative electrode active material layer is suppressed when the negative electrode has a curved folded structure. [Means for solving the problem]
[0007] An energy storage element according to one aspect of the present invention made to solve the above-mentioned problems comprises a negative electrode having a pair of flat portions facing each other and a curved folded portion connecting one end of the pair of flat portions, and a positive electrode arranged between the pair of flat portions of the negative electrode, wherein the negative electrode has a negative electrode base material and a negative electrode active material layer laminated directly or indirectly on a surface of the negative electrode base material in an unpressed or low-pressed state, the negative electrode active material layer contains a negative electrode active material, the negative electrode active material includes solid graphite particles, and the solid graphite particles have an aspect ratio of 1 or more and 5 or less.
[0008] An energy storage element according to another aspect of the present invention comprises a negative electrode having a pair of opposing flat portions and a curved folded portion connecting one end portion of the pair of flat portions, and a positive electrode disposed between the pair of flat portions of the negative electrode, wherein the negative electrode has a negative electrode substrate and a negative electrode active material layer laminated directly or indirectly on a surface of the negative electrode substrate, the negative electrode active material layer contains a negative electrode active material, the negative electrode active material includes solid graphite particles, the aspect ratio of the solid graphite particles is 1 or more and 5 or less, and a ratio Q2 / Q1 of a surface roughness Q2 of the negative electrode substrate in a region where the negative electrode active material layer is not disposed to a surface roughness Q1 of the negative electrode substrate in a region where the negative electrode active material layer is disposed is 0.90 or more. Effect of the Invention
[0009] According to the present invention, it is possible to provide an energy storage element in which the falling off of the negative electrode active material layer is suppressed when the negative electrode has a curved folded structure. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic exploded perspective view showing the configuration of an energy storage element according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic exploded perspective view of the positive electrode, the negative electrode, and the separator that constitute the electrode assembly in FIG. [Diagram 3] FIG. 3 is a schematic cross-sectional view for explaining the electrode body. [Figure 4] FIG. 4 is a schematic cross-sectional view showing an electrode assembly according to another embodiment of the present invention. [Diagram 5] FIG. 5 is a schematic diagram showing an embodiment of an electricity storage device configured by assembling a plurality of electricity storage elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] First, an overview of the energy storage element disclosed in this specification will be described.
[0012] An energy storage element according to one aspect of the present invention comprises a negative electrode having a pair of opposing flat portions and a curved folded portion connecting one end portion of the pair of flat portions, and a positive electrode disposed between the pair of flat portions of the negative electrode, wherein the negative electrode has a negative electrode base material and a negative electrode active material layer laminated directly or indirectly on a surface of the negative electrode base material in an unpressed or low-pressed state, the negative electrode active material layer contains a negative electrode active material, the negative electrode active material includes solid graphite particles, and the solid graphite particles have an aspect ratio of 1 or more and 5 or less.
[0013] In the case where the negative electrode of the storage element has a curved folded structure, the falling off of the negative electrode active material layer is suppressed. The reason for this is unclear, but it is considered as follows. When the storage element includes a negative electrode having a pair of flat parts facing each other and a curved folded part connecting one end of the pair of flat parts, and a positive electrode disposed between the pair of flat parts of the negative electrode, the negative electrode active material of the curved folded part does not face the positive electrode, so that it contributes little to the charge / discharge reaction. Therefore, when a negative electrode active material such as graphite that has a large volume change due to charging / discharging is contained, the flat part facing the positive electrode and the curved folded part not facing the positive electrode have different expansion rates of the negative electrode active material layer due to the insertion of lithium ions into the negative electrode active material during charging. Specifically, the negative electrode active material layer of the flat part facing the positive electrode is easily expanded, and the negative electrode active material layer of the curved folded part not facing the positive electrode is not easily expanded. Therefore, stress is applied to the interface between the curved folded portion and the flat portion, and the negative electrode active material layer of the folded portion, which is particularly susceptible to large stress, is likely to fall off from the negative electrode substrate. In contrast, the electric storage element includes a negative electrode in which a negative electrode active material layer containing solid graphite particles is arranged in a non-pressed or low-pressed state, and the negative electrode active material is hardly subjected to stress until the electrode body is formed. Therefore, the graphite particles themselves have little residual stress, and uneven expansion of the negative electrode active material layer caused by the release of residual stress can be suppressed. In addition, since the graphite particles contained in the negative electrode active material are solid, the density within the graphite particles is uniform, and the aspect ratio is 1 to 5, so that the graphite particles are close to a sphere, and current concentration is unlikely to occur, and uneven expansion of the negative electrode active material layer can be suppressed. Furthermore, since the graphite particles are close to a sphere, adjacent graphite particles are unlikely to get caught, and the graphite particles slide against each other moderately, and even if the graphite particles expand, they are likely to be maintained in a state close to close packing. In this way, even if the graphite particles expand, the graphite particles in the energy storage element expand relatively uniformly and slide over each other to an appropriate degree, thereby maintaining a negative electrode active material layer with a high packing rate of graphite particles, and thus suppressing the expansion of the negative electrode active material layer that occurs during initial charging. This is presumably why the stress applied to the interface between the curved folded portion and the flat portion of the negative electrode is reduced, suppressing the falling off of the negative electrode active material in the folded portion.
[0014] The term "non-pressed" means that no step of applying pressure (linear pressure) to the negative electrode active material layer is performed during production. The term "low pressure press" means that a step of applying a pressure (linear pressure) of less than 10 kgf / mm to the negative electrode active material layer is performed using a device designed to apply pressure to a workpiece, such as a roll press machine, during production. The term "aspect ratio" means the A / B value, which is the ratio of the longest diameter A of a particle to the longest diameter B in the direction perpendicular to the diameter A, in the cross section of the particle observed in an SEM image obtained using a scanning electron microscope.
[0015] An energy storage element according to one aspect of the present invention comprises a negative electrode having a pair of opposing flat portions and a curved folded portion connecting one end portion of the pair of flat portions, and a positive electrode disposed between the pair of flat portions of the negative electrode, wherein the negative electrode has a negative electrode substrate and a negative electrode active material layer laminated directly or indirectly on a surface of the negative electrode substrate, the negative electrode active material layer contains a negative electrode active material, the negative electrode active material comprises solid graphite particles, the aspect ratio of the solid graphite particles is 1 or more and 5 or less, and a ratio Q2 / Q1 of a surface roughness Q2 of the negative electrode substrate in a region where the negative electrode active material layer is not disposed to a surface roughness Q1 of the negative electrode substrate in a region where the negative electrode active material layer is disposed is 0.90 or more.
[0016] In a negative electrode in which a negative electrode active material layer is laminated on a negative electrode substrate, the stronger the pressure applied to the negative electrode active material layer, the rougher the surface of the negative electrode substrate in the region where the negative electrode active material layer is formed, and the smaller the Q2 / Q1. In other words, when no pressure is applied to the negative electrode active material layer, the negative electrode substrate has almost the same surface roughness in the region where the negative electrode active material layer is disposed and the region where the negative electrode active material layer is not disposed (for example, in the exposed region of the negative electrode substrate in the case where the negative electrode substrate is exposed on the negative electrode). That is, the Q2 / Q1 approaches 1. In the energy storage element, the Q2 / Q1 is 0.90 or more, which means that there is no or small pressure applied to the negative electrode active material layer. Therefore, the graphite particles themselves have little residual stress, and uneven expansion of the negative electrode active material layer caused by the release of residual stress can be suppressed. In addition, since the graphite particles contained in the negative electrode active material are solid, the density within the graphite particles is uniform, and since the graphite particles are close to a sphere due to the aspect ratio being 1 to 5, current concentration is unlikely to occur, and uneven expansion of the negative electrode active material layer can be suppressed. Furthermore, since the graphite particles are close to a sphere, adjacent graphite particles are unlikely to get caught, and the graphite particles slide against each other moderately, and even if the graphite particles expand, they tend to be maintained in a state close to close packing. In this way, even if the graphite particles expand, the electric storage element expands relatively uniformly and slides against each other moderately, so that the negative electrode active material layer with a high packing rate of the graphite particles is maintained, and expansion of the negative electrode active material layer that occurs during initial charging can be suppressed. Therefore, it is presumed that the stress applied to the interface between the curved folded portion and the flat portion of the negative electrode is eliminated or reduced, and the falling off of the negative electrode mixture at the folded portion is suppressed.
[0017] It is preferable that the negative electrode is a strip folded in a bellows-like shape along the longitudinal direction. When the negative electrode is a strip folded in a bellows-like shape along the longitudinal direction, it has a plurality of folded parts to which a particularly large stress is likely to be applied. In the energy storage element, the graphite particles contained in the negative electrode active material are solid, so that the density within the graphite particles is uniform, and the aspect ratio is 1 to 5, so that the graphite particles are close to a sphere, so that current concentration is unlikely to occur, and therefore, the expansion of the non-uniform negative electrode active material layer can be suppressed. Therefore, the energy storage element in which the negative electrode is a strip folded in a bellows-like shape along the longitudinal direction can more suitably exhibit the effect of applying the present configuration. Here, "bellows-like" refers to a structure in which mountain folds and valley folds are repeated. The curved shape of the folded part includes not only a curved shape formed with a circular arc, but also a bent shape.
[0018] Hereinafter, an energy storage device according to an embodiment of the present invention will be described in detail. Note that the names of the components (elementary components) used in each embodiment may differ from the names of the components (elementary components) used in the background art.
[0019] <Electricity storage element> [First embodiment] An electric storage element according to one embodiment of the present invention includes an electrode assembly, a non-aqueous electrolyte, and a case that contains the electrode assembly and the non-aqueous electrolyte. The electrode assembly has a negative electrode and a positive electrode. The non-aqueous electrolyte is impregnated in a separator and is interposed between the positive electrode and the negative electrode.
[0020] [Specific configuration of the energy storage element] Next, a non-aqueous electrolyte secondary battery will be described as an example of a specific configuration of an energy storage element according to one embodiment of the present invention. FIG. 1 is a schematic exploded perspective view showing the configuration of an energy storage element according to one embodiment of the present invention. FIG. 2 is a schematic exploded perspective view of a positive electrode, a negative electrode, and a separator constituting the electrode body of FIG. 1. As shown in FIG. 1, the energy storage element 1 includes a flat rectangular parallelepiped case 3 having an opening, a long and narrow rectangular plate-like lid body 6 capable of closing the long and narrow rectangular opening of the case 3, an electrode body 2 accommodated in the case 3, and a positive electrode terminal 4 and a negative electrode terminal 5 provided on the lid body 6. The case 3 accommodates a non-aqueous electrolyte together with the electrode body 2 in the internal space.
[0021] The top surface of the case 3 is closed by a lid 6. The case 3 and the lid 6 are made of a metal plate. The metal plate can be made of, for example, aluminum. The lid 6 is provided with a positive electrode terminal 4 and a negative electrode terminal 5 that are electrically connected to the outside. When the energy storage element 1 is a non-aqueous electrolyte energy storage element, a non-aqueous electrolyte (electrolytic solution) is injected into the case 3 through an injection hole (not shown) provided in the lid 6.
[0022] The positive electrode terminal 4 is an electrode terminal electrically connected to the positive electrode 14 of the electrode body 2 shown in FIG. 2, and the negative electrode terminal 5 is an electrode terminal electrically connected to the negative electrode 15 of the electrode body 2. In other words, the positive electrode terminal 4 and the negative electrode terminal 5 are metal electrode terminals for leading out electricity stored in the electrode body 2 to the external space of the energy storage element 1 and for introducing electricity into the internal space of the energy storage element 1 to store electricity in the electrode body 2. In this embodiment, the thickness direction (stacking direction) of the electrode body 2 is defined as the Y-axis direction, and the long axis direction in a cross section of the electrode body 2 perpendicular to the Y-axis is defined as the X-axis direction. In addition, the direction perpendicular to the Y-axis and the X-axis is defined as the Z-axis direction.
[0023] 2, the electrode body 2 is constructed by disposing separators 8 between alternately stacked positive electrodes 14 and negative electrodes 15. Specifically, the electrode body 2 is constructed by repeatedly stacking a negative electrode 15, a separator 8, a positive electrode 14, and a separator 8 in this order.
[0024] The non-aqueous electrolyte is interposed between the positive electrode 14 and the negative electrode 15 in a state of being impregnated in the separator 8. In Fig. 2, in order to illustrate the positive electrode 14 and the negative electrode 15, the positive electrode 14 arranged inside the two separators 8 arranged on the front side (the negative side in the Y-axis direction) is indicated by a dashed line. In order to prevent the positive electrode 14 and the negative electrode 15 from shorting out with each other, the separator 8 has a larger area than the positive electrode 14 and the negative electrode 15 when viewed from the stacking direction, and is stacked such that each end side is located outside the end sides of the positive electrode 14 and the negative electrode 15 (excluding the positive electrode tab 42 and the negative electrode tab 52).
[0025] In addition, a positive electrode tab 42 protruding toward the positive side (upward) of the positive electrode 14 in the Z axis direction is formed on the positive electrode 14. A negative electrode tab 52 protruding toward the positive side (upward) of the negative electrode 15 in the Z axis direction is formed on the negative electrode 15. The positive electrode tab 42 and the negative electrode tab 52 protrude upward beyond the end (upper end) of the separator 8 on the positive side in the Z axis direction. In the positive electrode tab 42, a positive electrode active material layer is not formed, and the positive electrode substrate is exposed. In the negative electrode tab 52, a negative electrode active material layer is not formed, and the negative electrode substrate is exposed.
[0026] FIG. 3 is a schematic cross-sectional view for explaining the electrode body. As shown in FIG. 3, the negative electrode 15 has a negative electrode substrate 32 and a negative electrode active material layer 31 that is superimposed on each of both sides of the negative electrode substrate 32. That is, the negative electrode 15 has one negative electrode substrate 32 and a pair of negative electrode active material layers 31 on both sides of the negative electrode substrate 32. The negative electrode 15 is in the form of a long sheet and has a curved folded portion 34. Specifically, the negative electrode 15 is a strip that is folded in an accordion-like shape along the longitudinal direction. The negative electrode 15 has a pair of flat portions 33 facing each other and a curved folded portion 34 that connects the ends of one side of the pair of flat portions 33. The positive electrode 14 is disposed between the curved folded portions 34. The sheet-like (plate-like) positive electrodes 14 are disposed so as to alternately face the flat portions 33 of the negative electrode 15. As shown in FIG. 1, the electrode body 2 is housed in the case 3 so that each flat portion 33 of the negative electrode 15 is parallel (approximately parallel) to the longitudinal direction (long side walls) of the case 3 (i.e., each folded portion 34 faces the short side walls).
[0027] The electrode body 2 has a negative electrode 15, a positive electrode member 40 including a positive electrode 14 and a separator 8. In the electrode body 2 of this embodiment, the positive electrode 14 and the separator 8 sandwiching the positive electrode 14 constitute the positive electrode member 40. The separator 8 is a sheet-shaped member having insulating properties, and is disposed between the negative electrode 15 and the positive electrode 14. As a result, in the electrode body 2, the negative electrode 15 and the positive electrode 14 are insulated from each other. The separator 8 also holds a non-aqueous electrolyte in the case 3. As a result, during charging and discharging of the energy storage element 1, charged ions can move between the negative electrode 15 and the positive electrode 14 that face each other with the separator 8 sandwiched therebetween. The separator 8 of this embodiment covers the entire positive electrode 14 so as to sandwich it. Specifically, the separator 8 is folded back at the center in the longitudinal direction so as to sandwich the positive electrode 14, and both end edges in the folding direction are joined by adhesion, welding, or the like. At this time, separator 8 is joined so that rectangular positive electrode tab 42 protrudes from folded separator 8. It should be noted that the shape of the separator of the energy storage element is not limited to that of separator 8 in this embodiment.
[0028] As shown in FIG. 3, the positive electrode 14 has a positive electrode substrate 37 and a pair of positive electrode active material layers 36 on both sides of the positive electrode substrate 37. On the other hand, the positive electrode tab 42 does not have the positive electrode active material layer 36, and the positive electrode substrate 37 is exposed. The positive electrode 14 is disposed inside the curved folded portion 34 of the negative electrode 15, which is a strip folded in a bellows shape along the longitudinal direction. Specifically, the positive electrode 14 is disposed between each of the adjacent flat portions 33 of the negative electrode 15. Therefore, the electrode body 2 of this embodiment has a plurality of positive electrodes 14. The positive electrode active material layer 36 of the positive electrode 14 faces the negative electrode active material layer 31 of the flat portion 33 of the negative electrode 15.
[0029] Returning to FIG. 1, a positive electrode current collector (not shown) is disposed on the positive electrode terminal 4 side above the electrode assembly 2. Positive electrode tabs 42 extending from each of the positive electrodes 14 are bundled together and electrically connected to the positive electrode terminal 4 via the positive electrode current collector. A negative electrode current collector (not shown) is disposed on the negative electrode terminal 5 side above the electrode assembly 2. Negative electrode tabs 52 extending from each flat portion of the negative electrode 15 are bundled together and electrically connected to the negative electrode terminal 5 via the negative electrode current collector.
[0030] [Negative electrode] The negative electrode includes a negative electrode substrate and a negative electrode active material layer laminated directly or indirectly on at least one surface of the negative electrode substrate. The negative electrode active material layer of the first embodiment of the present invention is arranged in a non-pressed or low-pressed state.
[0031] (Negative electrode substrate) The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, and nickel-plated steel, or alloys thereof, are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils and vapor-deposited films, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil. The term "electrically conductive" refers to a material having a volume resistivity of 1×10 as measured in accordance with JIS-H0505 (1975). 7 "Non-conductive" means that the volume resistivity is 1×10 7 This means that the resistance is greater than Ω·cm.
[0032] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, even more preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, the strength of the negative electrode substrate can be increased while increasing the energy density per volume of the storage element. The "average thickness of the substrate" refers to the value obtained by dividing the punched mass when a substrate of a given area is punched out by the true density and punched area of the substrate.
[0033] (Negative electrode active material layer) The negative electrode active material layer is disposed along at least one surface of the negative electrode substrate directly or via an intermediate layer, and is formed from a so-called negative electrode mixture that contains a negative electrode active material.
[0034] In the energy storage element according to the first embodiment of the present invention, the negative electrode active material contains solid graphite particles. By containing the solid graphite particles in the negative electrode active material, it is possible to suppress the expansion of the negative electrode active material layer that occurs during initial charging. In addition, the negative electrode active material may contain other negative electrode active materials in addition to the solid graphite particles.
[0035] (Solid graphite particles) "Solid" means that the inside of the particle is filled and there is substantially no void. More specifically, "solid" means that the area ratio of the cross section of the particle observed in an SEM image obtained using a scanning electron microscope (SEM) excluding the voids in the particle to the total area of the particle is 95% or more. In a preferred embodiment, the area ratio of the solid graphite particles can be 97% or more (e.g., 99% or more). Moreover, "graphite" is a carbon material having an average lattice spacing d(002) of the (002) plane measured by X-ray diffraction method before charging and discharging or in a discharged state of less than 0.34 nm. Here, "discharged state" refers to a state in which the open circuit voltage is 0.7 V or more in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic Li as a counter electrode. Since the potential of the metallic Li counter electrode in an open circuit state is approximately equal to the redox potential of Li, the open circuit voltage in the single-electrode battery is approximately equal to the potential of the negative electrode containing the carbon material relative to the redox potential of Li. In other words, an open circuit voltage of 0.7 V or more in the single-electrode battery means that lithium ions capable of being absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material.
[0036] The area ratio T of a graphite particle, excluding voids within the particle, to the area of the entire particle, can be determined by the following procedure. (1) Preparation of the measurement sample The graphite particle powder to be measured is fixed in a thermosetting resin. A cross-section polisher is used to expose the cross section of the graphite particle fixed in the resin, and the measurement sample is prepared. (2) Acquiring SEM images To obtain SEM images, a JSM-7001F (manufactured by JEOL Ltd.) scanning electron microscope is used. SEM images are obtained by observing secondary electron images. The acceleration voltage is 15 kV. The observation magnification is set so that 3 to 15 graphite particles appear in one field of view. The obtained SEM image is saved as an image file. Other conditions such as spot diameter, working distance, irradiation current, brightness, and focus are appropriately set so that the contours of the graphite particles are clearly visible. (3) Cutting out the outline of the graphite particles The image cutting function of the image editing software Adobe Photoshop Elements 11 is used to cut out the outlines of the graphite particles from the acquired SEM image. This cutting out of the outlines is performed by using the quick selection tool to select the area outside the outlines of the active material particles, and editing everything except the graphite particles to a black background. If the outlines of less than three graphite particles could be cut out at this time, another SEM image is acquired and the process is repeated until the outlines of three or more graphite particles can be cut out. (4) Binarization The image of the first graphite particle among the cut-out graphite particles is binarized using the image analysis software PopImaging 6.00, with a threshold value set to a concentration 20% lower than the concentration at which the intensity is at its maximum. The area of the lower concentration side is calculated through the binarization process, and this is taken as the "area S1 excluding voids within the particle." Next, the image of the first graphite particle, the same as before, is subjected to a binarization process with a threshold density of 10. Through the binarization process, the outer periphery of the graphite particle is determined, and the area inside the outer periphery is calculated to obtain the "area S0 of the entire particle." Using the S1 and S0 calculated above, the ratio of S1 to S0 (S1 / S0) is calculated to calculate the "area ratio T1 excluding voids within the particle to the entire particle area" for the first graphite particle. The above binarization process is also performed on the images of the second and subsequent graphite particles among the cut-out graphite particles, and the areas S1 and S0 are calculated. The area ratios T2, T3, ... of each graphite particle are calculated based on the calculated areas S1 and S0. (5) Determination of area ratio T The "area ratio T of the graphite particles excluding the voids within the particles to the total area of the particles" is determined by calculating the average value of all the area ratios T1, T2, T3, ... calculated by the binarization process.
[0037] The solid graphite particles can be appropriately selected from various known graphite particles. Examples of such known graphite particles include natural graphite particles and artificial graphite particles. Here, natural graphite is a general term for graphite extracted from natural minerals, and artificial graphite is a general term for graphite produced artificially. Specific examples of natural graphite particles include flake graphite, lump graphite (flake graphite), and earthy graphite. The solid graphite particles can be natural graphite particles having a flat flake shape, or spherical natural graphite particles obtained by spheroidizing the flake graphite. As the solid graphite particles, natural graphite particles or artificial graphite particles may be used. However, since artificial graphite generally has a smaller specific surface area than natural graphite particles, artificial graphite particles are more preferable from the viewpoint of durability, such as suppressing the formation of a film accompanying a charge / discharge reaction. In addition, the above-mentioned artificial graphite particles may be graphite particles having a coating (e.g., an amorphous carbon coating) applied to the surface.
[0038] The R value of the solid graphite particles can be generally 0.25 or more (e.g., 0.25 to 0.8), for example, 0.28 or more (e.g., 0.28 to 0.7), typically 0.3 or more (e.g., 0.3 to 0.6). In some embodiments, the R value of the solid graphite particles may be 0.5 or less, or may be 0.4 or less. Here, the "R value" refers to the peak intensity of the G band in the Raman spectrum (I G1 ) versus D band peak intensity (I D1 ) ratio (I D1 / I G1 ).
[0039] Here, the "Raman spectrum" is obtained by performing Raman spectroscopy using "HR Revolution" manufactured by Horiba Ltd. under the conditions of a wavelength of 532 nm (YAG laser), a grating of 600 g / mm, and a measurement magnification of 100 times. -1 From 4000cm -1 Raman spectroscopy was performed in the range of 4000cm -1 The minimum value in the range is taken as the base intensity, and normalized by the maximum intensity in the above measurement range (for example, the intensity of the G band). Next, the obtained curve is fitted using a Lorentz function, and the 1580 cm -1 Nearby G band and 1350 cm -1 The intensity of each of the D bands in the vicinity was calculated, and the "G band peak intensity (I G1 ) and D band peak intensity (I D1 )".
[0040] The lower limit of the aspect ratio of the solid graphite particles is 1 (e.g., 1.5), and preferably 2.0. In some embodiments, the aspect ratio of the solid graphite particles may be 2.2 or more (e.g., 2.5 or more, e.g., 2.7 or more). On the other hand, the upper limit of the aspect ratio of the solid graphite particles may be 5 (e.g., 4.5), and preferably 4.0. In some embodiments, the aspect ratio of the solid graphite particles may be 3.5 or less (e.g., 3.0 or less). By setting the aspect ratio of the solid graphite particles in the above range, the graphite particles become closer to a sphere, and current concentration is less likely to occur, so that non-uniform expansion of the negative electrode active material layer can be suppressed.
[0041] The aspect ratio can be determined as follows. (1) Preparation of the measurement sample A measurement sample is used in which the cross section used in determining the above-mentioned area ratio T is exposed. (2) Acquiring SEM images To obtain the SEM image, a scanning electron microscope JSM-7001F (manufactured by JEOL Ltd.) is used. The SEM image is obtained by observing a secondary electron image. The acceleration voltage is 15 kV. The observation magnification is set so that 100 to 1000 negative electrode active material particles appear in one field of view. The obtained SEM image is saved as an image file. Other conditions such as spot diameter, working distance, irradiation current, brightness, and focus are appropriately set so that the contours of the negative electrode active material particles are clearly visible. (3) Determining the aspect ratio From the acquired SEM image, 100 negative electrode active material particles are randomly selected, and for each, the longest diameter A of the negative electrode active material particle and the longest diameter B in the direction perpendicular to diameter A are measured, and the A / B value is calculated. The aspect ratio of the negative electrode active material particle is determined by calculating the average value of all the calculated A / B values.
[0042] The lower limit of the average particle size of the solid graphite particles is preferably 1 μm, more preferably 2 μm. The upper limit of the average particle size is generally 10 μm (e.g., 8 μm). The upper limit of the average particle size is preferably 5 μm, more preferably 4.5 μm. In some embodiments, the median diameter of the solid graphite particles may be 4 μm or less, or 3.5 μm or less (e.g., 3 μm or less). The technology disclosed herein can be preferably implemented in an embodiment in which the average particle size of the solid graphite particles is 1 μm or more and less than 5 μm (further 1.5 μm or more and 4.5 μm or less, particularly 2 μm or more and 4 μm or less). When the average particle size of the solid graphite particles is within the above range, ease of handling during production can be improved.
[0043] Specifically, the median diameter (D50) that is the "average particle diameter" can be measured by the following method. Measurements are performed using a laser diffraction particle size distribution analyzer (Shimadzu Corporation's "SALD-2200") as the measuring device and Wing SALD-2200 as the measurement control software. A scattering measurement mode is used, and a laser beam is irradiated onto a wet cell in which a dispersion liquid in which the measurement sample is dispersed in a dispersion solvent is circulated, to obtain a scattered light distribution from the measurement sample. The scattered light distribution is then approximated by a log-normal distribution, and the particle diameter at a cumulative degree of 50% is taken as the median diameter (D50). Suitable examples of the solid graphite particles disclosed herein include those having a median diameter (D50) of 5 μm or less and an aspect ratio of 1 to 5; those having a median diameter (D50) of 4.5 μm or less and an aspect ratio of 1.5 to 4.5; those having a median diameter (D50) of 4 μm or less and an aspect ratio of 1.8 to 4; those having a median diameter (D50) of 3 μm or less and an aspect ratio of 2 to 3.5; etc. By using solid graphite particles having an aspect ratio and median diameter (D50) within such a predetermined range, the above-mentioned effects can be better exhibited.
[0044] The true density of the solid graphite particles is 2.1 g / cm 3 The use of solid graphite particles having such a high true density makes it possible to increase the energy density. On the other hand, the upper limit of the true density of the solid graphite particles is, for example, 2.5 g / cm. 3 The true density is measured by a gas volumetric method using a pycnometer with helium gas. The BET specific surface area of the solid graphite particles is not particularly limited, but is, for example, 3 m 2 / g or more. By using solid graphite particles having such a large BET specific surface area, the above-mentioned effects can be more effectively exhibited. The BET specific surface area of the solid graphite particles is preferably 3.2 m 2 / g or more, more preferably 3.5m 2 / g or more, more preferably 3.7m 2 The upper limit of the BET specific surface area of the solid graphite particles is, for example, 10 m 2The solid graphite particles preferably have a BET specific surface area of 8 m 2 / g or less, more preferably 6m 2 / g or less, more preferably 5m 2 The BET specific surface area of solid graphite particles is determined by measuring the pore size distribution by the one-point method using nitrogen gas adsorption.
[0045] The solid graphite particles may be, for example, spherical or non-spherical. Specific examples of non-spherical shapes include chunks, spindles, flakes, plates, ellipses, and eggs. Among these, chunks of solid graphite particles are preferred. The solid graphite particles may have irregularities on the surface. The solid graphite particles may include particles formed by agglomeration of a plurality of graphite particles.
[0046] The lower limit of the content of the solid graphite particles relative to the total mass of the negative electrode active material is preferably 60 mass%, more preferably 70 mass%. In some embodiments, the content of the solid graphite particles relative to the total mass of the negative electrode active material may be, for example, 75 mass% or more, or may be 80 mass%. By making the content of the solid graphite particles equal to or more than the lower limit, the charge / discharge efficiency can be further improved. On the other hand, the upper limit of the content of the solid graphite particles relative to the total mass of the negative electrode active material may be, for example, 100 mass%.
[0047] (Other negative electrode active materials) The negative electrode active material layer disclosed herein may contain other negative electrode active materials in addition to the solid graphite particles, as long as the effects of the present invention are not impaired. Examples of the other negative electrode active materials include hollow graphite particles, carbonaceous active materials such as non-graphitized carbonaceous active materials, and non-carbonaceous active materials.
[0048] Examples of non-graphitizable carbonaceous active materials include non-graphitizable carbon and graphitizable carbon. Here, "non-graphitizable carbon" refers to a carbon material having an average lattice spacing d(002) of the (002) plane measured by X-ray diffraction before charging and discharging or in a discharged state of 0.36 nm or more and 0.42 nm or less. "Graphitizable carbon" refers to a carbon material having d(002) of 0.34 nm or more and less than 0.36 nm. When a non-graphitizable carbonaceous active material is contained, it is appropriate that the mass of the solid graphite particles is 70 mass% or more of the total mass of the carbonaceous active material contained in the negative electrode active material layer, preferably 80 mass% or more, and more preferably 90 mass% or more. Among them, an electric storage element in which 100 mass% of the carbonaceous active material contained in the negative electrode active material layer is the solid graphite particles is preferable.
[0049] Examples of the non-carbonaceous active material include semimetals such as Si, metals such as Sn, oxides of these metals, or composites of these with carbon materials. The content of the non-carbonaceous active material is, for example, 30 mass% or less of the total mass of the negative electrode active material contained in the negative electrode active material layer, preferably 20 mass% or less, and more preferably 10 mass% or less. The technology disclosed herein can be preferably implemented in an embodiment in which the total proportion of the carbonaceous active material in the total mass of the negative electrode active material contained in the negative electrode active material layer is greater than 90 mass%. The proportion of the carbonaceous active material is more preferably 95 mass% or more, even more preferably 98 mass% or more, and particularly preferably 99 mass% or more. Among these, a storage element in which 100 mass% of the negative electrode active material contained in the negative electrode active material layer is a carbonaceous active material is preferred.
[0050] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but the lower limit is preferably 50 mass%, more preferably 80 mass%, and even more preferably 90 mass%, while the upper limit of this content is preferably 99 mass%, more preferably 98 mass%.
[0051] (Other optional ingredients) The negative electrode active material layer disclosed herein contains optional components such as a conductive agent, a binder, a thickener, and a filler, as necessary.
[0052] The solid graphite particles also have electrical conductivity, and examples of the conductive agent include carbonaceous materials, metals, and conductive ceramics. Examples of the carbonaceous materials include graphitized carbon, non-graphitized carbon, and graphene-based carbon. Examples of non-graphitized carbon include carbon nanofibers, pitch-based carbon fibers, and carbon black. Examples of carbon black include furnace black, acetylene black, and ketjen black. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), and fullerene. Examples of the conductive material include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more may be mixed and used. These materials may also be used in combination. For example, a material in which carbon black and CNT are combined may be used. Among these, carbon black is preferred from the viewpoint of electronic conductivity and coatability, and acetylene black is preferred among these.
[0053] When a conductive agent is used in the negative electrode active material layer, the proportion of the conductive agent in the entire negative electrode active material layer can be approximately 8.0 mass % or less, and usually is preferably approximately 5.0 mass % or less (for example, 1.0 mass % or less).
[0054] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, and polyimide; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; and polysaccharide polymers.
[0055] The content of the binder in the negative electrode active material layer is preferably from 1% by mass to 10% by mass, more preferably from 3% by mass to 9% by mass. By setting the content of the binder in the above range, the negative electrode active material particles can be stably held.
[0056] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, this functional group may be deactivated in advance by methylation or the like.
[0057] The filler is not particularly limited. Examples of the main component of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof.
[0058] When a filler is used in the negative electrode active material layer, the ratio of the filler to the entire negative electrode active material layer can be about 8.0 mass % or less, and usually, it is preferably about 5.0 mass % or less (e.g., 1.0 mass % or less). In this specification, the term "main component" means the component with the highest content, for example, a component contained in an amount of 50 mass % or more relative to the total mass.
[0059] The lower limit of the density of the negative electrode active material layer is 1.20 g / cm 3 is preferred, and 1.30 g / cm 3 More preferably, 1.40 g / cm 3 On the other hand, the upper limit of the density of the negative electrode active material layer is 1.55 g / cm. 3 is preferred, and 1.50 g / cm 3 In some embodiments, the density of the negative electrode active material layer is 1.45 g / cm 3When the density of the negative electrode active material layer is within the above range, it is possible to obtain an energy storage element in which expansion of the negative electrode active material layer and falling off of the negative electrode active material layer at the folded portion, which occur during initial charging, are suppressed.
[0060] The porosity of the negative electrode active material layer is preferably 40% or less. By setting the porosity of the negative electrode active material layer to 40% or less, the energy density of the electric storage element can be further increased. In addition, the porosity of the negative electrode active material layer is preferably 25% or more. By using graphite particles that are solid and have an aspect ratio set to 1 to 5 as the negative electrode active material, the electric storage element can have a small porosity even when the negative electrode active material layer is in an unpressed or low-pressed state. Therefore, the energy density of the electric storage element can be effectively increased while suppressing the falling off of the negative electrode active material layer. In this respect, the technical value is also high.
[0061] (Middle class) The intermediate layer is a coating layer on the surface of the negative electrode substrate, and contains conductive particles such as carbon particles to reduce the contact resistance between the negative electrode substrate and the negative electrode active material layer. The intermediate layer may cover a part of the negative electrode substrate, or may cover the entire surface. The negative electrode substrate may have an area where the intermediate layer is laminated and where the negative electrode active material layer is not laminated. The configuration of the intermediate layer is not particularly limited, and may be formed, for example, from a composition containing a resin binder and conductive particles.
[0062] [Positive electrode] The positive electrode has a positive electrode substrate and a positive electrode active material layer. The positive electrode active material layer contains a positive electrode active material. The positive electrode active material layer is laminated directly or via an intermediate layer along at least one surface of the positive electrode substrate.
[0063] The positive electrode substrate has electrical conductivity. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or alloys thereof are used. Among these, aluminum and aluminum alloys are preferred in terms of the balance between potential resistance, high electrical conductivity, and cost. In addition, the form of the positive electrode substrate may be foil, vapor deposition film, or the like, and foil is preferred in terms of cost. That is, aluminum foil is preferred as the positive electrode substrate. In addition, examples of aluminum or aluminum alloys include A1085, A3003, etc., as specified in JIS-H4000 (2014).
[0064] The positive electrode active material layer is formed from a so-called positive electrode mixture containing a positive electrode active material. The positive electrode mixture forming the positive electrode active material layer further contains optional components such as a conductive agent, a binder, a thickener, and a filler as necessary.
[0065] The positive electrode active material can be appropriately selected from, for example, known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as a positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni 1-x ]O2(0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γCo β Al (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn (2-γ) O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more of them may be mixed and used. In the positive electrode active material layer, one of these compounds may be used alone, or two or more of them may be mixed and used. The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but the lower limit is preferably 50 mass%, more preferably 80 mass%, and even more preferably 90 mass%. On the other hand, the upper limit of this content is preferably 99% by mass, more preferably 98% by mass.
[0066] The conductive agent is not particularly limited as long as it is a conductive material. Such a conductive agent can be selected from the materials exemplified for the negative electrode. When a conductive agent is used, the proportion of the conductive agent in the entire positive electrode active material layer can be about 1.0 mass% or more and 20 mass% or less, and usually, it is preferably about 2.0 mass% or more and 15 mass% or less (for example, 3.0 mass% or more and 6.0 mass% or less).
[0067] Examples of the binder include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc. When a binder is used, the proportion of the binder in the entire positive electrode active material layer can be about 0.50 mass% or more and 15 mass% or less, and is usually preferably about 1.0 mass% or more and 10 mass% or less (for example, 1.5 mass% or more and 3.0 mass% or less).
[0068] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium, it is preferable to deactivate the functional group in advance by methylation or the like. When a thickener is used, the ratio of the thickener to the entire positive electrode active material layer can be about 8% by mass or less, and is usually preferably about 5.0% by mass or less (for example, 1.0% by mass or less).
[0069] The filler can be selected from the materials exemplified for the negative electrode. When a filler is used, the proportion of the filler in the entire positive electrode active material layer can be about 8.0 mass % or less, and usually, it is preferably about 5.0 mass % or less (for example, 1.0 mass % or less).
[0070] The intermediate layer is a coating layer on the surface of the positive electrode substrate, and contains conductive particles such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The intermediate layer may cover a part of the positive electrode substrate, or may cover the entire surface. As with the negative electrode, the configuration of the intermediate layer is not particularly limited, and may be formed, for example, from a composition containing a resin binder and conductive particles.
[0071] [Separator] As the separator, for example, a woven fabric, a nonwoven fabric, a porous resin film, etc. are used. Among these, a porous resin film is preferable from the viewpoint of strength, and a nonwoven fabric is preferable from the viewpoint of nonaqueous electrolyte retention. As the main component of the separator, a polyolefin such as polyethylene or polypropylene is preferable from the viewpoint of strength, and a polyimide or aramid is preferable from the viewpoint of oxidation decomposition resistance. These resins may also be combined.
[0072] An inorganic layer may be laminated between the separator and the electrode (usually, the positive electrode). This inorganic layer is a porous layer also called a heat-resistant layer. A separator having an inorganic layer formed on one or both sides of a porous resin film may also be used. The inorganic layer is usually composed of inorganic particles and a binder, and may contain other components.
[0073] [Non-aqueous electrolyte] The non-aqueous electrolyte may be a known non-aqueous electrolyte that is generally used in a general non-aqueous electrolyte secondary battery (electric storage element). The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte may be a solid electrolyte or the like.
[0074] The non-aqueous solvent may be a known non-aqueous solvent that is generally used as a non-aqueous solvent for a general non-aqueous electrolyte for a storage element. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, esters, ethers, amides, sulfones, lactones, and nitriles. Among these, it is preferable to use at least a cyclic carbonate or a chain carbonate, and it is more preferable to use a cyclic carbonate and a chain carbonate in combination. When a cyclic carbonate and a chain carbonate are used in combination, the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is not particularly limited, but is preferably, for example, 5:95 to 50:50.
[0075] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, catechol carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate, with EC being preferred.
[0076] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, and the like. Among these, EMC is preferable.
[0077] The electrolyte salt may be any known electrolyte salt that is commonly used as an electrolyte salt for a general non-aqueous electrolyte for a storage element, such as lithium salt, sodium salt, potassium salt, magnesium salt, onium salt, etc., with lithium salt being preferred.
[0078] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a hydrocarbon group in which hydrogen is replaced by fluorine such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.
[0079] The lower limit of the concentration of the electrolyte salt in the nonaqueous electrolyte is 0.1 mol / dm 3 is preferred, and 0.3 mol / dm 3 More preferably, 0.5 mol / dm 3 More preferably, 0.7 mol / dm 3On the other hand, the upper limit is not particularly limited, but is preferably 2.5 mol / dm 3 is preferred, and 2.0 mol / dm 3 More preferably, 1.5 mol / dm 3 is more preferred.
[0080] The non-aqueous electrolyte may contain other additives. Furthermore, the non-aqueous electrolyte may be, for example, a room temperature molten salt or an ionic liquid.
[0081] The energy storage element according to the first embodiment of the present invention has a strip-shaped negative electrode folded in a bellows-like shape along the longitudinal direction, and has a plurality of folded parts that are susceptible to large stress. The graphite particles contained in the negative electrode active material of this energy storage element are solid, so that the density within the graphite particles is uniform, and the aspect ratio is 1 to 5, so that the graphite particles are nearly spherical, making it difficult for current concentration to occur, and therefore it is possible to suppress non-uniform expansion of the negative electrode active material layer. Therefore, the effect of applying this configuration can be more suitably exhibited in the energy storage element in which the negative electrode is a strip-shaped negative electrode folded in a bellows-like shape along the longitudinal direction.
[0082] [Second embodiment] In the energy storage element according to the second embodiment of the present invention, the negative electrode active material contains solid graphite particles, and the aspect ratio of the solid graphite particles is 1 or more and 5 or less. The ratio Q2 / Q1, which is the ratio of the surface roughness Q2 of the negative electrode base material in the region where the negative electrode active material layer is not arranged to the surface roughness Q1 of the negative electrode base material in the region where the negative electrode active material layer is arranged (for example, the exposed region of the negative electrode base material when the negative electrode has a portion where the negative electrode base material is exposed), is 0.90 or more. The configuration other than the above configuration is the same as that of the first embodiment, so that a duplicated description will be omitted. The more pressure is applied to the negative electrode base material, the rougher the region where the negative electrode active material layer is formed becomes, and therefore the above Q2 / Q1 becomes smaller. In other words, when no pressure is applied, the surface roughness of the negative electrode base material is almost the same in the region where the negative electrode active material layer is arranged and the region where the negative electrode active material layer is not arranged (for example, the exposed region of the negative electrode base material when the negative electrode has a portion where the negative electrode base material is exposed). That is, Q2 / Q1 approaches 1. In the energy storage element, the above Q2 / Q1 is 0.90 or more, and the pressure applied to the negative electrode active material layer is in a state where there is no pressure or is small. Therefore, the graphite particles themselves have little residual stress, and the expansion of the negative electrode active material layer caused by the release of the residual stress can be suppressed. In addition, since the graphite particles are solid, the density within the graphite particles is uniform, and the aspect ratio is 1 to 5, so that the graphite particles are close to a sphere, and current concentration is unlikely to occur, so that the expansion of the negative electrode active material layer can be suppressed. In addition, since the graphite particles are close to a sphere as described above, the orientation of the graphite particles arranged in the active material layer is low and the orientation is likely to be random, so that the expansion of the negative electrode active material layer can be suppressed. Furthermore, since the graphite particles are close to a sphere, adjacent graphite particles are unlikely to get caught, and the graphite particles slide against each other moderately, and even if the graphite particles expand, they are likely to be maintained in a state close to close packing. Thus, in the present invention, even if the graphite particles expand, they expand relatively uniformly and slide over each other appropriately, thereby maintaining a negative electrode active material layer with a high packing rate of graphite particles. As a result, it is presumed that the expansion of the negative electrode active material layer that occurs during initial charging can be suppressed.
[0083] The above-mentioned "surface roughness" refers to the center line roughness Ra of the surface of the substrate (in the region where the active material layer and other layers are formed, the surface after removing these layers) measured with a laser microscope in accordance with JIS-B0601 (2013). Specifically, it can be a value measured by the following method.
[0084] First, if the negative electrode has a portion where the negative electrode substrate is exposed, the surface roughness of this portion is taken as the surface roughness Q2 of the region where the negative electrode active material layer is not disposed, and is measured in accordance with JIS-B0601 (2013) using a commercially available laser microscope (manufactured by Keyence Corporation, device name "VK-8510"). At this time, the measurement conditions are a measurement region (area) of 149 μm × 112 μm (16688 μm 2 ), the measurement pitch is 0.1 μm. Next, the negative electrode is shaken using an ultrasonic cleaner to remove the negative electrode active material layer and other layers from the negative electrode substrate, and the surface roughness Q1 of the region where the negative electrode active material layer was formed is measured in the same manner as the surface roughness of the portion where the negative electrode substrate is exposed. Note that, when there is no portion where the negative electrode substrate is exposed in the negative electrode (for example, when the entire surface of the negative electrode substrate is covered with an intermediate layer described later), the surface roughness of the region where the negative electrode active material layer was not disposed (for example, the region covered with the intermediate layer and where the negative electrode active material layer was not disposed) is measured in the same manner as the surface roughness Q2 of the region where the negative electrode active material layer is not disposed.
[0085] The lower limit of the surface roughness ratio (Q2 / Q1) is preferably 0.92, more preferably 0.94, since the pressure applied to the negative electrode active material layer is zero or small, while the upper limit of the surface roughness ratio (Q2 / Q1) is preferably 1.10, more preferably 1.05.
[0086] In the energy storage element, when the negative electrode has a curved folded structure, the negative electrode active material layer is prevented from falling off.
[0087] [Method of manufacturing the energy storage element] The manufacturing method of the energy storage element of this embodiment can be appropriately selected from known methods. The manufacturing method includes, for example, preparing an electrode body, preparing a non-aqueous electrolyte, and housing the electrode body and the non-aqueous electrolyte in a case. Preparing the electrode body includes preparing a positive electrode and a negative electrode, and forming the electrode body by stacking the positive electrode and the negative electrode via a separator. The electrode body is composed of a negative electrode having a pair of flat parts facing each other and a curved folded part connecting one end of the pair of flat parts, and a sheet-like (plate-like) positive electrode arranged between the pair of flat parts of the negative electrode.
[0088] In the process of preparing the negative electrode, for example, a negative electrode active material layer containing a negative electrode active material containing solid graphite particles is laminated along at least one surface of the negative electrode substrate by coating the negative electrode mixture on the negative electrode substrate. Specifically, for example, the negative electrode active material layer is laminated by coating the negative electrode mixture on the negative electrode substrate and drying it. After the drying, the negative electrode active material layer is pressed or the low pressure pressing described above is performed before laminating the negative electrode and the positive electrode.
[0089] The process of housing the non-aqueous electrolyte in the case can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution is injected from an injection port formed in the case, and then the injection port is sealed. Details of the other elements constituting the storage element obtained by this manufacturing method are as described above.
[0090] [Other embodiments] The energy storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and a part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, a part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.
[0091] In FIG. 3, the separator 8 in the above embodiment is formed by folding one sheet body, but it may be configured to be formed by joining two sheets bodies.
[0092] Although the separator 8 in the above embodiment is laminated on the positive electrode 14 side, it may be laminated on the negative electrode 15 side. In this case, the separator 8 may be in a zigzag shape (a zigzag shape having a plurality of folds) similar to the negative electrode 15.
[0093] In the energy storage element 1 of the above embodiment, the negative electrode is a strip-shaped body folded in a bellows-like shape along the longitudinal direction, but the present invention is not limited to this configuration. In the electrode body 2, it is sufficient that one of the electrodes has at least one curved folded portion. FIG. 4 is a schematic cross-sectional view showing an electrode body of another embodiment of the present invention. The energy storage element 60 includes a sheet-shaped negative electrode 75 having a pair of flat portions 73 facing each other and a curved folded portion 74 connecting one end of the pair of flat portions 73, and a sheet-shaped (plate-shaped) positive electrode 14 arranged to alternately face the flat portions 73 of the negative electrode 75. In this case, the multiple positive electrode members 40 are also sandwiched between the curved folded portions 74 of the negative electrode 75. Since the energy storage element includes a negative electrode in which the negative electrode active material layer containing the solid graphite particles is arranged in an unpressed or low-pressed state, this configuration also suppresses expansion of the negative electrode active material layer that occurs during initial charging, reduces stress on the mixture of the curved folded portion, and suppresses falling off of the negative electrode active material layer at the folded portion. Furthermore, even in an unpressed or low-pressed state, the negative electrode active material layer of the energy storage element can reduce the porosity of the negative electrode active material layer, thereby increasing the energy density. In the embodiment shown in FIG. 4, the folded portions 74 are arranged in alternate directions, but they may be arranged in the same direction.
[0094] In the above embodiment, the description has been given mainly of the case where the power storage element is a non-aqueous electrolyte secondary battery, but other power storage elements may be used. Examples of other power storage elements include capacitors (electric double layer capacitors, lithium ion capacitors), etc. Examples of non-aqueous electrolyte secondary batteries include lithium ion non-aqueous electrolyte secondary batteries.
[0095] The present invention can also be realized as an electricity storage device including a plurality of the above-mentioned electricity storage elements. Also, a battery pack can be formed by using one or a plurality of the electricity storage elements (cells) of the present invention, and further, an electricity storage device can be formed by using this battery pack. The electricity storage device can be used as a power source for automobiles such as electric vehicles (EVs), hybrid vehicles (HEVs), plug-in hybrid vehicles (PHEVs), etc. Furthermore, the electricity storage device can be used in various power supply devices such as engine starting power supply devices, auxiliary power supply devices, and uninterruptible power supplies (UPS).
[0096] 5 shows an example of an energy storage device 30 in which energy storage units 20, each of which is an assembly of two or more electrically connected energy storage elements 1, are further assembled. The energy storage device 30 may include a bus bar (not shown) that electrically connects the two or more energy storage elements 1, and a bus bar (not shown) that electrically connects the two or more energy storage units 20. The energy storage units 20 or the energy storage device 30 may include a status monitoring device (not shown) that monitors the status of the one or more energy storage elements. EXAMPLES
[0097] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0098] [Preparation of negative electrodes in Examples 1 and 2 and Comparative Examples 1 to 6] A negative electrode mixture paste was prepared containing the negative electrode active material of the composition shown in Table 1, styrene-butadiene rubber as a binder, and carboxymethyl cellulose as a thickener, with water as a dispersion medium. The ratio of the negative electrode active material, binder, and thickener was 97.4:2.0:0.6 by mass. The negative electrode mixture paste was applied to both sides of a negative electrode substrate (surface roughness 0.74 μm) made of copper foil with a thickness of 8 μm, and dried to form a negative electrode active material layer, thereby obtaining negative electrodes of Examples 1 and 2 and Comparative Examples 1 to 6. The physical properties of the negative electrode active material measured by the method shown below and the presence or absence of a pressing process are shown in Table 1. The coating amount of the negative electrode active material layer (the negative electrode mixture paste from which the dispersion medium has been evaporated) per unit area on one side after drying was 1.55 g / 100 cm. 2 The negative electrode of Example 2 was pressed using a roll press at a pressure (linear pressure) of less than 10 kgf / mm, and the negative electrodes of Comparative Examples 1, 2, 4, and 6 were pressed at a pressure (linear pressure) of 40 kgf / mm or more. 2 / g of lump solid graphite was used.
[0099] [Preparation of Energy Storage Elements in Examples 1 and 2 and Comparative Examples 1 to 6] An energy storage element including a negative electrode having a curved folded portion was produced by the following procedure. An electrode assembly was produced using the negative electrodes of Examples 1 and 2 and Comparative Examples 1 to 6 shown in Table 1, the positive electrode described below, and a polyethylene separator having a thickness of 20 μm. 1 / 3 Co 1 / 3 Mn 1 / 3 A positive electrode mixture paste was prepared containing O2, polyvinylidene fluoride (PVDF) as a binder, acetylene black as a conductive agent, and N-methyl-2-pyrrolidone (NMP) as a dispersion medium. The ratio of the positive electrode active material, binder, and conductive agent was 94:3:3 by mass. The positive electrode mixture paste was applied to both sides of a positive electrode substrate made of aluminum foil with a thickness of 12 μm, and dried to form a positive electrode active material layer. The amount of the positive electrode mixture (the dispersion medium evaporated from the positive electrode mixture paste) applied per unit area on one side after drying was 2.1 g / 100 cm.2 Then, pressing was performed using a roll press. The positive electrode, negative electrode, and separator were laminated to produce the electrode body shown in Fig. 2 and Fig. 3. Next, LiPF6 was added as an electrolyte salt at a concentration of 1.2 mol / dm to a non-aqueous solvent obtained by mixing EC, EMC, and DMC in a volume ratio of 30:35:35. 3 A non-aqueous electrolyte solution was prepared by mixing the above components so as to obtain a content of 1:1. Thereafter, the non-laminated portion of the positive electrode substrate and the non-laminated portion of the negative electrode substrate were welded to the positive electrode current collector and the negative electrode current collector, respectively, and then sealed in a case. Next, after the case and the cover plate were welded together, the non-aqueous electrolyte was poured in and the opening was sealed. In this manner, the energy storage elements of Example 1, Example 2, and Comparative Example 1 to Comparative Example 6 were obtained.
[0100] [evaluation] (Density of negative electrode active material layer) The density of the negative electrode active material layer is determined by the amount of the negative electrode active material layer applied, W (g / 100 cm 2 ), the thickness of the negative electrode active material layer before charge and discharge, which will be described later, is T (cm), and it can be calculated by the following formula. Density of the negative electrode active material layer (g / cm 3 )=W / (T×100)
[0101] (Surface roughness ratio of negative electrode substrate) The surface roughness Q1 of the region where the negative electrode active material layer was formed and the surface roughness Q2 of the portion of the negative electrode where the negative electrode base material was exposed were measured using a laser microscope as described above. Then, the ratio (Q2 / Q1) of the surface roughness of the negative electrode base material was calculated using the measured Q1 and Q2. Here, when measuring the surface roughness Q1 of the region where the negative electrode active material layer was formed, the negative electrode active material layer was removed by immersing and shaking the sample in water for 3 minutes and in ethanol for 1 minute using a Branson tabletop ultrasonic cleaner 2510J-DTH.
[0102] (Measurement of thickness of negative electrode active material layer before charging and discharging) Ten samples of 2 cm x 1 cm area of the negative electrode before the production of the storage element were prepared as measurement samples, and the thickness of each negative electrode was measured using a high-precision digital micrometer manufactured by Mitutoyo Corporation. The thickness of the negative electrode was measured at five points for each negative electrode, and the thickness of the negative electrode active material layer before charging and discharging was measured by subtracting the thickness of the negative electrode substrate (8 μm) from the average value. The thickness of the negative electrode active material layer before charging and discharging was calculated by averaging the thicknesses of the negative electrode active material layer before charging and discharging measured for the ten negative electrodes.
[0103] (Measurement of thickness of negative electrode active material layer at full charge) For the energy storage elements of the examples and comparative examples before charging and discharging, the current density was 2 mA / cm 2 , and the charge termination current density was 0.04 mA / cm 2 The battery was initially charged at a constant current / constant voltage (CCCV) with an upper limit voltage of 4.25 V to a fully charged state. The thickness of the negative electrode active material layer in the fully charged state was then measured. The thickness of the negative electrode active material layer in the fully charged state was measured in a glove box filled with argon having a dew point value of -60°C or lower, in the same manner as in the measurement of the thickness of the negative electrode active material layer before charging / discharging, except that the fully charged electricity storage element was disassembled and the negative electrode after DMC cleaning was used as the measurement sample.
[0104] (Measurement of the amount of expansion of the negative electrode active material during initial charging) The amount of expansion of the negative electrode active material during initial charging was calculated by subtracting the "thickness of the negative electrode active material layer before charging and discharging" from the "thickness of the negative electrode active material layer at full charge" calculated by the above-mentioned method.
[0105] (Measurement of porosity of negative electrode active material layer) The porosity of the negative electrode active material layer is a calculated value calculated from the mass of the components contained in the negative electrode active material layer, the true density, and the thickness of the negative electrode active material layer. Specifically, it is calculated by the following formula. Porosity of negative electrode active material layer (%)={1-(density of negative electrode active material layer / true density of negative electrode active material layer)}×100 Here, the "density of the negative electrode active material layer" (g / cm 3 ) is calculated from the coating amount W of the negative electrode active material layer and the thickness T of the negative electrode active material layer before charge and discharge, as described above. "True density of the negative electrode active material layer" (g / cm 3 ) is calculated from the true density value of each component contained in the negative electrode active material layer and the mass of each component. Specifically, the true density of the negative electrode active material is expressed as D1 (g / cm 3 ), the true density of the binder is D2 (g / cm 3 ), and the true density of the thickener is D3 (g / cm 3 ), the mass of the negative electrode active material contained in 1 g of the negative electrode active material layer is W1 (g), the mass of the binder contained in 1 g of the negative electrode active material layer is W2 (g), and the mass of the thickener contained in 1 g of the negative electrode active material layer is W3 (g), then the mass is calculated using the following formula. True density of the negative electrode active material layer (g / cm 3 )=1 / {(W1 / D1)+(W2 / D2)+(W3 / D3)}
[0106] (Evaluation of mixture falling off of the folded part of the negative electrode) After the initial charge, the current density was set to 2mA / cm 2 Then, the battery was discharged at a constant current (CC) with a lower limit voltage of 2.75 V to be in a discharged state. The discharged electricity storage element was disassembled and visually observed to judge whether or not the negative electrode active material layer in the folded portion of the negative electrode had fallen off.
[0107] The following Table 1 shows the results of evaluation of the area ratio T of the negative electrode active material particles excluding the voids within the particles, the aspect ratio of the graphite particles, the density of the negative electrode active material layer, the surface roughness ratio Q2 / Q1 of the negative electrode base material, the thickness of the negative electrode active material layer before charging and discharging, the thickness of the negative electrode active material layer at full charge, the amount of expansion of the negative electrode active material at initial charging, the porosity of the negative electrode active material layer, and the falling off of the negative electrode active material layer at the folded portion of the negative electrode. The area ratio T and aspect ratio of the graphite particles used were calculated by the method described above.
[0108] [Table 1]
[0109] As shown in Table 1, in Examples 1 and 2, which include a negative electrode having a pair of opposing flat portions and a curved folded portion connecting one end of the pair of flat portions, a positive electrode disposed between the pair of flat portions of the negative electrode, in which the negative electrode active material layer is disposed in an unpressed or low-pressed state, the aspect ratio of the solid graphite particles as the negative electrode active material is 1 or more and 5 or less, and the surface roughness ratio Q2 / Q1 of the negative electrode base material is 0.90 or more, the expansion amount of the negative electrode active material layer during initial charging was small, and falling off of the negative electrode active material layer at the folded portion was suppressed.
[0110] On the other hand, in Comparative Examples 1, 2, 4, and 6 in which the negative electrode active material layer was arranged in a pressed state and the surface roughness ratio Q2 / Q1 of the negative electrode substrate was less than 0.90, the expansion amount of the negative electrode active material at the time of initial charging was significantly increased compared to Examples 1 and 2. In addition, even though the negative electrode active material layer was arranged in a non-pressed or low-pressed state and the surface roughness ratio Q2 / Q1 of the negative electrode substrate was 0.90 or more, in Comparative Example 3 in which hollow graphite particles were used as the negative electrode active material and Comparative Example 5 in which the aspect ratio was more than 5, the expansion amount of the negative electrode active material at the time of initial charging of the negative electrode active material layer was increased compared to Examples 1 and 2.
[0111] Furthermore, in terms of the porosity of the negative electrode active material layer, when comparing Example 1, Comparative Example 3, and Comparative Example 5 in which the negative electrode active material layer was arranged in an unpressed state, it is found that Example 1 had a small porosity even though the negative electrode active material layer was arranged in an unpressed state, and thus it was possible to increase the filling rate of the negative electrode active material.
[0112] As described above, it was shown that when the negative electrode of the energy storage element has a curved folded structure, the expansion of the negative electrode active material layer and the falling off of the negative electrode active material layer at the folded portion that occur during initial charging are suppressed. [Industrial Applicability]
[0113] The present invention is suitably used as an electricity storage element, including a non-aqueous electrolyte secondary battery used as a power source for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]
[0114] 1 Energy storage element 2, 60 electrode body 3 Cases 4 Positive terminal 5 Negative terminal 6 Lid 8 Separator 14 Positive electrode 15, 75 negative electrode 20 Energy Storage Unit 30 Energy storage device 31, 71 Negative electrode active material layer 32, 72 Anode substrate 33, 73 flat area 34, 74 Folding section 36 Positive electrode active material layer 37 Positive electrode substrate 40 Positive electrode material 42 Positive tab 52 Negative tab
Claims
1. a negative electrode having a pair of flat portions facing each other and a curved folded portion connecting one end of each of the pair of flat portions; a plate-shaped positive electrode disposed between the pair of flat portions of the negative electrode; It is equipped with the negative electrode has a negative electrode substrate and a negative electrode active material layer laminated on a surface of the negative electrode substrate, the negative electrode active material layer is formed on both of the pair of flat portions and the folded portion, The negative electrode active material layer contains a negative electrode active material, the negative electrode active material contains solid graphite particles, A method for producing an electric storage element, wherein the solid graphite particles have an aspect ratio of 1 or more and 5 or less, preparing a negative electrode by directly or indirectly laminating a negative electrode active material layer on a surface of a negative electrode substrate; and forming an electrode body by stacking the negative electrode and the positive electrode with a separator interposed therebetween; A method for producing an electric storage element, comprising the steps of: not pressing the negative electrode active material layer before laminating the negative electrode and the positive electrode; or performing low-pressure pressing on the negative electrode active material layer.
2. a negative electrode having a pair of flat portions facing each other and a curved folded portion connecting one end of each of the pair of flat portions; a plate-shaped positive electrode disposed between the pair of flat portions of the negative electrode; It is equipped with The negative electrode has a negative electrode substrate and a negative electrode active material layer laminated directly or indirectly on a surface of the negative electrode substrate, the negative electrode active material layer is formed on both of the pair of flat portions and the folded portion, The negative electrode active material layer contains a negative electrode active material, the negative electrode active material contains solid graphite particles, The solid graphite particles have an aspect ratio of 1 or more and 5 or less, A storage element in which a ratio Q2 / Q1 of a surface roughness Q2 of the negative electrode substrate in a region where the negative electrode active material layer is not disposed to a surface roughness Q1 of the negative electrode substrate in a region where the negative electrode active material layer is disposed is 0.90 or more and 1.00 or less.
3. 3. The electric storage element according to claim 2, wherein the negative electrode is a strip folded in a bellows shape along the longitudinal direction.
Citation Information
Patent Citations
Electrochemical element, lithium secondary battery and set battery and manufacture thereof
JP1994140077A
Positive electrode material for lithium secondary battery and its synthesis and evaluation, and lithium secondary battery and its manufacture
JP1994290780A
Negative pole material for lithium battery, and lithium battery
JP2005222933A
Negative electrode for secondary battery and secondary battery using the same
JP2007207439A
Power storage element and manufacturing method thereof
JP2014103082A